2007
DOI: 10.1086/513569
|View full text |Cite
|
Sign up to set email alerts
|

GSTT1andGSTM1Null Genotypes May Facilitate Hepatitis C Virus Infection Becoming Chronic

Abstract: Oxidative stress contributes to hepatitis C virus (HCV)-induced liver damage. The activity of antioxidant glutathione S-transferases (GSTs) T1 and M1 is polymorphic. The GSTT1 and GSTM1 genotypes were identified in 139 HCV-infected patients and in 329 healthy individuals. Among patients, there was an excess of GSTT1 (odds ratio [OR], 2.76 [95% confidence interval [CI], 1.77-4.30]; P<.001) and GSTM1 (OR, 1.54 [95% CI, 1.02-2.35]; P=.032) null genotypes and of double-null haplotypes (OR, 3.65 [95% CI, 1.98-6.75]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…In addition, we investigated whether GSTT1 and GSTM1 gene variations play a role in liver fibrosis caused by hepatitis C virus and found that individuals with the null variant of both GSTT1 and GSTM1 have considerably increased risk of advanced fibrosis. This result was in agreement with a previous study in Spain (27). Martinez et al recruited 139 HCV-infected Spanish patients and 329 healthy controls to estimate the association between both gene polymorphisms and chronic phase of HCV-induced liver disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we investigated whether GSTT1 and GSTM1 gene variations play a role in liver fibrosis caused by hepatitis C virus and found that individuals with the null variant of both GSTT1 and GSTM1 have considerably increased risk of advanced fibrosis. This result was in agreement with a previous study in Spain (27). Martinez et al recruited 139 HCV-infected Spanish patients and 329 healthy controls to estimate the association between both gene polymorphisms and chronic phase of HCV-induced liver disease.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, genetic polymorphisms of antioxidant enzymes could modify the capacity to alleviate oxidative stress and thereby influence the progression of liver damage. However, there have been few studies on the effects of GST gene polymorphism on the disease progression of HBV infection (25,26), but so far we have not seen any reports about that association in the investigation of the relationship between GST gene polymorphism and stage of liver fibrosis in HCV-infected patients in Taiwan, only one report in Spain (27).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed a marked excess of the combined GSTM1/GSTT1 double‐null genotype in the case of chronic HCV Egyptian patients compared with a healthy control group. This is in accordance with the results obtained in Spanish (Martinez et al., ) and Taiwanese studies (Sun et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Another effect that ROS appear to have on HCV is an increase in HCV genome heterogeneity, which may contribute to the evolutional survival of the virus by ensuring viral escape from the immune system (during establishment of infection as well as during treatment) [158, 159]. Indeed, patients with a null genotype of glutathione-S-transferases, namely gstt1 and gstm1 , are characterized by decreased rates of the spontaneous resolution of acute HCV infection [160]. …”
Section: Hepatitis C Virusmentioning
confidence: 99%